2018
DOI: 10.5194/hess-22-2937-2018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of capillary rise and recirculation on simulated crop yields

Abstract: Abstract. Upward soil water flow is a vital supply of water to crops. The purpose of this study is to determine if upward flow and recirculated percolation water can be quantified separately, and to determine the contribution of capillary rise and recirculated water to crop yield and groundwater recharge. Therefore, we performed impact analyses of various soil water flow regimes on grass, maize and potato yields in the Dutch delta. Flow regimes are characterized by soil composition and groundwater depth and de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Shallow groundwater (SGW) is an important source for irrigation and food production in many countries, and also serves as an important secondary source of water supply during natural droughts [13]. Furthermore, the state of the SGW table plays an important role in groundwater-dependent ecosystems [14], and thanks to capillary action, SGW, and therefore its level, also has an effect on surface vegetation and yield of agricultural crops [15,16]. Consequently, any decline in the water table, due to changes in precipitation patterns and rises in temperature, can reduce well yield and increase pumping costs.…”
Section: Introductionmentioning
confidence: 99%
“…Shallow groundwater (SGW) is an important source for irrigation and food production in many countries, and also serves as an important secondary source of water supply during natural droughts [13]. Furthermore, the state of the SGW table plays an important role in groundwater-dependent ecosystems [14], and thanks to capillary action, SGW, and therefore its level, also has an effect on surface vegetation and yield of agricultural crops [15,16]. Consequently, any decline in the water table, due to changes in precipitation patterns and rises in temperature, can reduce well yield and increase pumping costs.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, soil moisture simulated by mHM for deeper soil layers is more dynamic and it is still strictly coupled to the atmospheric forcing. As this dynamic could be relevant also for capturing land surface fluxes (Kollet & Maxwell, ; Kroes et al, ), comparisons with groundwater observations are highly recommended even when groundwater prediction is not intended to identify limitations also for other simulated states and land surface fluxes. Simple parametrizations to account for groundwater contributions on ET should be, for instance, included also in mHM to partially compensate this unresolved hydrological process (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently Kroes et al (2018) analysed the impact of capillary rise and recirculation of percolation water below grassland, maize and potatoes in Dutch soils. They concluded that soil water and crop growth modelling should consider both capillary rise from groundwater and recirculation of percolation water as this improves the accuracy of yield simulations.…”
Section: Capillary Risementioning
confidence: 99%